Emergence of the Islamic State and Challenges for Af-Pak Region - Sohail Ahmad; Mahwish Bakht (Journal of Political Studies, 2018)
The Islamic State was hoping for a smooth establishment and extraordinary gains in the Khorasan region. The presence of US forces in Afghanistan and Operation Zarb-eAzb by the strong military of Pakistan did not allow it to happen. The Taliban could be a strong ally of IS in the region but clashes between the two had diminished the chances of its establishment and success in the Khorasan region. Both organizations have declared ‘Jihad’ against each other to enjoy monopoly status in the region, especially in Afghanistan. Afghan government even supported Taliban to fight against IS. Though IS has claimed many deadly attacks in Afghanistan and Pakistan it has not gained the momentum and support it was expecting. The nature of this study is qualitative.